Semantic Unification of the Gray Zone Phenomenon on the Example of Military and Economic-Legal Spheres: A Systemic Perspective - Ilia E. Sapan (RUDN Journal of Philosophy)
The research deals with the phenomenon of gray zones on the example of military and economic-legal spheres using the systemic-communicative approach, arising on the basis of Niklas Luman’s social theory. The author analyzes the nature of gray zones, their historical evolution and contemporary significance in the conditions of globalization and technological progress. It is argued that gray zones often serve as catalysts of social change and require a comprehensive approach to understand and regulate them. The novelty of the work lies in the fact that for the first time an attempt has been made to semantically unify the concept of “gray zone” through the prism of Luhmann’s systemic-communicative theory, with the justification of the possibility of its application in different functional systems of society. The author argues that gray hones represent areas of uncertainty, namely, aggregates of heterogeneous communications that do not participate in the reproduction (autopoiesis) of social systems. Relying on the systemic-communicative approach, the gray zone can be seen as something that a social system cannot interpret in the logic of its own communications. The author emphasizes the importance of systems analysis for identifying structural and functional problems associated with gray zones and suggests methods for their investigation and classification. Also discussed are ways in which a systems-communicative approach can be used to better understand the complex interactions between different social systems are also discussed. It is concluded that unifying the concept of the gray zone facilitates more effective communication and cooperation between specialists from different fields, and improves the development of policies and educational programs.